2019
DOI: 10.1155/2019/3741909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Asymmetrical Dimethylarginine Detection in Patients with Connective Tissue Disease-Associated Pulmonary Arterial Hypertension

Abstract: Objective. To evaluate the clinical value of serum asymmetrical dimethylarginine (ADMA) in patients with connective tissue disease- (CTD-) associated pulmonary arterial hypertension (PAH). Methods. 88 patients with CTD were recruited between December 2017 and August 2018 in Jiangxi Provincial People’s Hospital. Patients were further divided into two groups: CTD-without PAH (n = 45 cases) and CTD-with PAH (n = 43 cases), according to the pulmonary systolic blood pressure measured by echocardiography. 40 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…A more potent inhibitor of NO synthesis than SDMA (30), ADMA has been shown to associate with hemodynamic indices and survival in prior studies of PAH patients (25,31). In the current study, we found that that high ADMA levels associated with lower 6MWD in PAH patients on ERAs but not in PAH patients on either PDE-5i or on PDE-5i/ ERA combination therapy.…”
Section: Discussionsupporting
confidence: 54%
“…A more potent inhibitor of NO synthesis than SDMA (30), ADMA has been shown to associate with hemodynamic indices and survival in prior studies of PAH patients (25,31). In the current study, we found that that high ADMA levels associated with lower 6MWD in PAH patients on ERAs but not in PAH patients on either PDE-5i or on PDE-5i/ ERA combination therapy.…”
Section: Discussionsupporting
confidence: 54%
“…A more potent inhibitor of NO synthesis than SDMA [30], ADMA has been shown to associate with hemodynamic indices and survival in prior studies of PAH patients [25,31]. In the current study, we found that that high ADMA levels associated with lower 6MWD in PAH patients on ERAs but not in PAH patients on either PDE-5i or on PDE-5i/ ERA combination therapy.…”
Section: Discussionsupporting
confidence: 51%
“…A more potent inhibitor of NO synthesis than SDMA (24), ADMA has been shown to associate with hemodynamic indices and survival in prior studies of PAH patients (19,25). In the current study, we found that that high ADMA levels associated with lower 6MWD in PAH patients on ERAs but not in PAH patients on either PDE-5i or on PDE-5i/ ERA combination therapy.…”
Section: Discussionsupporting
confidence: 51%